2012
DOI: 10.1152/ajpregu.00483.2011
|View full text |Cite
|
Sign up to set email alerts
|

Acid secretion by mitochondrion-rich cells of medaka (Oryzias latipes) acclimated to acidic freshwater

Abstract: In the present study, medaka embryos were exposed to acidified freshwater (pH 5) to investigate the mechanism of acid secretion by mitochondrion-rich (MR) cells in embryonic skin. With double or triple in situ hybridization/immunocytochemistry, the Na(+)/H(+) exchanger 3 (NHE3) and H(+)-ATPase were localized in two distinct subtypes of MR cells. NHE3 was expressed in apical membranes of a major proportion of MR cells, whereas H(+)-ATPase was expressed in basolateral membranes of a much smaller proportion of MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 50 publications
0
34
2
Order By: Relevance
“…The noninvasive SIET was previously applied to reveal acid (H ϩ ) secretion by yolk-sac ionocytes in zebrafish (9, 29) and FW-acclimated medaka (18,40). Herein, we used the same approach to show that ionocytes secrete H ϩ to acidify the yolk sac surface of medaka larva in SW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The noninvasive SIET was previously applied to reveal acid (H ϩ ) secretion by yolk-sac ionocytes in zebrafish (9, 29) and FW-acclimated medaka (18,40). Herein, we used the same approach to show that ionocytes secrete H ϩ to acidify the yolk sac surface of medaka larva in SW.…”
Section: Discussionmentioning
confidence: 99%
“…In zebrafish larvae, both H ϩ -ATPase and the Na ϩ /H ϩ exchanger (NHE3) in apical membranes contribute to H ϩ secretion by yolk-sac ionocytes (HR cells) (11). However, in the case of medaka acclimated to FW, only NHE3 was found in apical membranes of ionocytes (40); H ϩ -ATPase was found in basolateral membranes of a minor population of ionocytes but did not contribute to H ϩ secretion (18). In SW-acclimated medaka, H ϩ -ATPase was not detected in ionocytes by IHC (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the rates of Cl − uptake in larval (Bayaa et al, 2009) and adult zebrafish (Boisen et al, 2003), catfish (Goss et al, 1992) and rainbow trout (reviewed in Goss et al, 1994) have been reported as 200-700 μmol kg −1 h −1 , and are therefore comparable to the rates of HCO 3 − secretion (and thus Cl − uptake) in post-fed dogfish sharks. Additionally, basolateral VHA has been reported in gill ionocytes from freshwater stingray (Piermarini and Evans, 2001;Piermarini et al, 2002), bull shark (Reilly et al, 2011), killifish (Katoh et al, 2003) and rainbow trout (Tresguerres et al, 2006a), as well as in skin ionocytes from medaka embryos (Lin et al, 2012). An early study found evidence for Cl − /HCO 3 − exchange in the osmoconforming hagfish, and proposed that the driving force for the evolution of ion uptake in freshwater fish was A/B regulation (Evans, 1984).…”
Section: List Of Abbreviationsmentioning
confidence: 95%
“…Rhag occurs in red blood cells, while Rhcg and Rhbg occur in the apical and basolateral membranes, respectively, of the branchial epithelium. On the apical membrane, the deprotonation of NH 4 + at the cytoplasmic side of the Rhcg channel may provide a source of H + ions to drive Na + uptake under circumstances such as low external pH (Hirata et al, 2003;Kumai and Perry, 2011;Lin et al, 2012;Shih et al, 2012), which otherwise would seem thermodynamically challenging (Parks et al, 2008). In two studies, increased water Na + concentration resulted in elevated ammonia excretion (Shih et al, 2012;Wood et al, 2007).…”
Section: Introductionmentioning
confidence: 99%